An Empirical Study on Performance of Unit Linked Pension Plans of Selective Private Sector Life Insurance Companies - Khurana, Ashok (Indian Journal of Finance, 2009)
Retirement planning is a universal term today. The need to accumulate for the future and to make sure that a good life follows after retiring from work is the central reason that gives rise to the entire concept of retirement planning. Though people plan for their retirement by saving some money, it might lead to dearth of funds during the critical years. It is at such a point of time that the advantage of retirement planning becomes obvious. The increasing life span, impact of inflation, falling rate of fixed return, self dependence, breakdown of joint family system, unintended emergencies, increasing medical costs, coping with family health problems are the major reasons which adds to the magnitude of retirement planning. Indians are very much clear so far as their pension funds are concerned. Pension funds are used as a tool by them to fulfill their retirement needs. French insurance major AXA, with its global research on retirement revealed that Indians find life insurance the most suitable retirement planning tool followed by bank deposits. As much as 75% of the working population and 55% of the retired respondents in India cited life insurance as their primary tool for accumulating retirement funds. Hence, the trust and dependence of Indians on the life insurance companies for accumulation of funds is obvious.